2018
DOI: 10.4322/rbcv.2018.007
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização físico-química do colostro de búfalas na primeira ordenha pós-parto por meio de absorção infravermelha

Abstract: Objetivou-se caracterizar o colostro da primeira ordenha de búfalas da raça Murrah utilizando a metodologia não oficial de absorção infravermelha. Para isso, foram colhidas amostras individuais de 42 fêmeas multíparas, por meio de ordenha manual. As amostras foram coletadas em até 12 h após o parto e encaminhadas para determinação de gordura, proteína, lactose, sólidos totais e sólidos não gordurosos por meio de absorção infravermelha. Realizamos também a contagem de células somáticas (CCS) e leitura de condut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The means in the present study were also higher than the findings of Micinski et al (2017), in which the authors reported concentrations of 15.13% in the first milking, 9.19% in the second milking, and 4.51% on the third day of lactation in confined Holstein colostrum. The high protein concentration in this period may related to the higher amount of casein and immunoglobulins (IgG, IgA and IgM) in colostrum, as these immunoglobulins have the function of protecting the calf from diarrhea and other gastrointestinal diseases which represent more than 62% of mortality cases in newborns (Baumrucker et al 2010;Oliveira et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The means in the present study were also higher than the findings of Micinski et al (2017), in which the authors reported concentrations of 15.13% in the first milking, 9.19% in the second milking, and 4.51% on the third day of lactation in confined Holstein colostrum. The high protein concentration in this period may related to the higher amount of casein and immunoglobulins (IgG, IgA and IgM) in colostrum, as these immunoglobulins have the function of protecting the calf from diarrhea and other gastrointestinal diseases which represent more than 62% of mortality cases in newborns (Baumrucker et al 2010;Oliveira et al 2018).…”
Section: Discussionmentioning
confidence: 99%